Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3171/2018.8.jns172897
|View full text |Cite
|
Sign up to set email alerts
|

Reporting trends of p values in the neurosurgical literature

Abstract: OBJECTIVEThe objective of this study was to evaluate the trends in reporting of p values in the neurosurgical literature from 1990 through 2017.METHODSAll abstracts from the Journal of Neurology, Neurosurgery, and Psychiatry (JNNP), Journal of Neurosurgery (JNS) collection (including Journal of Neurosurgery: Spine and Journal of Neurosurgery: Pediatrics), Neurosurgery (NS), and Journal of Neurotrauma (JNT) available on PubMed from 1990 through 2017 were retrieved. Automated text mining was performed to extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Previous studies have also demonstrated the presence of publication bias in the neurosurgical literature. 4,7 One of the studies, restricted to 16 studies that considered the surgical treatment of unruptured intracranial aneurysms, concluded that failure to publish is not a random event. 4 They noticed that “neurosurgeons have very limited motivation to publish their results unless their combined mortality and morbidity is less than 10%.” This indicated that there is preferential publication of papers, where studies with positive clinical outcomes are more likely to be published than those that do not.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated the presence of publication bias in the neurosurgical literature. 4,7 One of the studies, restricted to 16 studies that considered the surgical treatment of unruptured intracranial aneurysms, concluded that failure to publish is not a random event. 4 They noticed that “neurosurgeons have very limited motivation to publish their results unless their combined mortality and morbidity is less than 10%.” This indicated that there is preferential publication of papers, where studies with positive clinical outcomes are more likely to be published than those that do not.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the dichotomization of P values and emphasis on “statistical significance” has demonstrable effects on the reporting of results in the biomedical literature. Many studies have shown not only a positive skew in the distribution of reported P values but also a large step-change in the P value distribution at 0.05 [ 30 33 ]. Such presence of systematic bias in the literature is likely to have far-reaching consequences[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Publication bias and selective reporting are a known issue in biomedical research [100], and neurosurgical research is not immune to this [101]. Fewer than half of U.S. clinical trials have complied with the law on reporting results [102].…”
Section: Case Registries Obligation To Publish and Long-term Follow-u...mentioning
confidence: 99%